LAND USE, INTERNAL MOBILITY AND EXTERNAL IMMIGRATION IN ITALY - CELI, Giuseppe; VITI, Domenico (Annals of Spiru Haret University. Economic Series, 2018)
After the Second World War, the economic development ofItalyhas profoundly changed the use of land. The paper investigates economic and regulatory implications of land withdrawal inItalyand the nexus with internal and foreign migration. The dualistic character of Italian economic development induced, especially in the 1950s and 1960s, huge migration flows from southern regions to the North, with strong repercussions in terms of abandonment of farmland and urban congestion. In recent times, in the light of increasing pressures from globalization, a revival of internal migration flows from the South to the North has occurred inItaly, but with different characteristics and implications with respect to the past. The interaction between internal mobility and foreign immigration (a new phenomenon forItaly, traditionally an emigration country) entails possible economic contra-indications but also new opportunities for rural development.